2004
DOI: 10.1089/107999004322813336
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginsengInduces Production of Proinflammatory Cytokines via Toll-like Receptor

Abstract: Ginseng radix, the dried root of Panax ginseng C. A. Meyer, has been shown to enhance the ability to resist microbial infections. Proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-alpha), interleukin-1beta (IL-1beta), IL-6, and interferon-gamma (IFN-gamma) are produced by macrophages treated with ginseng radix extract (GRE) in vitro as well as in vivo. However, the molecular mechanisms of the production are still not clear. In the present study, we demonstrated that production of TNF-alpha an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…Regarding immunological mechanism, it seems that gΔnef might indirectly result from the enhancement of innate immunity than adaptive immunity [30][31][32], immune modulation toward Th1-cytokines [33,34], antiinflammatory response through TLR4 induced NFkB [35] as well as the attenuation of hyper-immune activation state [12,16]. In particular, it appears that the LTR region including gΔnef is more fragile to KRG intake than are other regions of HIV-1 because HIV-1 gene expression is modulated by cis-acting regulatory elements in the LTRs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding immunological mechanism, it seems that gΔnef might indirectly result from the enhancement of innate immunity than adaptive immunity [30][31][32], immune modulation toward Th1-cytokines [33,34], antiinflammatory response through TLR4 induced NFkB [35] as well as the attenuation of hyper-immune activation state [12,16]. In particular, it appears that the LTR region including gΔnef is more fragile to KRG intake than are other regions of HIV-1 because HIV-1 gene expression is modulated by cis-acting regulatory elements in the LTRs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Nakaya et al reported that the production of TNF-α and IFN-γ was induced by ginseng saponins in spleen cells and peritoneal macrophages from C3H/HeN mice but not C3H/HeJ mice (29). Ginsan, a polysaccharide extract, markedly downregulated the production of proinflammatory cytokines (30).…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, a mechanistic study demonstrated that spleen cells and peritoneal macrophage cells that were stimulated by ginseng extract produced tumor necrosis factor-a and IFN-c inflammatory cytokines in a Toll-like receptor-4-dependent manner. 23 In contrast, ginseng was shown to attenuate lipopolysaccharide-induced pro-inflammatory mediators, including tumor necrosis factor-a and IL-6 in a macrophage cell line. 24 It is interesting that these immunosuppressive effects were not observed when ginseng was added after lipopolysaccharide stimulation of macrophage cells.…”
Section: Discussionmentioning
confidence: 97%
“…The nature of these activities and their underlying mechanisms remain largely unknown and were reported to be diverse depending on types of diseases and/or biological assessment methods: some studies demonstrated anti-inflammatory activities, while others reported proinflammatory effects. [22][23][24][25][26] Previous clinical studies demonstrated the beneficial effects of ginseng intake. A group of older adults who received daily oral administration of ginseng and influenza virus vaccination showed fewer cases of laboratory-confirmed influenza-like illness compared with the vaccination-only group.…”
Section: Introduction Imentioning
confidence: 99%